Nidificación del Halcón Peregrino (Falco peregrinus) en la precordillera de Barreal, San Juan, Argentina - Fava, Gustavo Alfredo; Fava, Gabriel Andrés; Acosta, Juan Carlos (Nuestras Aves, 2012)
Este artículo no cuenta con un resumen.